Linking network targets and site capabilities: A conceptual framework to determine site contributions to strategic manufacturing network targets. Issue 12 (7th December 2015) - Thomas, Simone; Scherrer-Rathje, Maike; Fischl, Maria; Friedli, Thomas
Abstract : Purpose: – To cope with the increasing challenges of globalisation, various manufacturing companies have established intra-company manufacturing networks. The purpose of this paper is to link the strategic network targets (i.e. accessibility, thriftiness represented by economies of scale and economies of scope, mobility, and learning) with the capabilities and characteristics of the constituting sites of the manufacturing network and thus facilitate the identification of mismatches and the discussion of possible development paths for the network. Design/methodology/approach: – The authors derive a conceptual framework from the literature which is tested with a single case; a manufacturing network consisting of eight manufacturing sites. Case data were collected based on 24 interviews with operations managers at network level and a standardised online survey among the sites' management teams. Findings: – Results indicate that manufacturing network and site levels need to be related when striving for a fit between manufacturing strategy, network strategy, and site capabilities and characteristics. Research limitations/implications: – Single case studies have only limited generalisability. Nevertheless, the case demonstrates the usefulness of several dimensions when analysing manufacturing networks on site and network level. Originality/value: – This paper represents the first attempt to link strategic targets of intra-company manufacturing networks with site capabilities and characteristics. Thereby, it provides a theoretical basis for future research on the relationship between strategic targets of manufacturing networks and their fulfilment. The developed manufacturing site portfolio, moreover, extends the site role typology discussion by a multi-dimensional perspective and represents a starting point for a multi-faceted discussion of site roles.